Ventral extradural spinal meningeal cyst causing cord compression: neurosurgical treatment Cisto meníngeo extradural ventral do canal espinhal causando compressão medular: tratamento neurocirúrgico - Daniel Monte-Serrat Prevedello; Cláudio Esteves Tatsui; Andrei Koerbel; César Vinícius Grande; Joacir Graciolli Cordeiro; João Cândido Araújo (Arquivos de Neuro-Psiquiatria)
Spinal extradural meningeal cysts are typically formed by a thin fibrotic membranous capsule, macroscopically similar that of an arachnoid membrane, filled by cerebro spinal fluid and related to a nerve root or to the posterior midline. Ventral location is extremely rare and when it occurs they usually cause spinal cord herniation through the ventral dural gap. A 61 year-old man who began with a two years long history of insidious tetraparesis, spasticity and hyperreflexia in lower extremities, and flaccid atrophy of upper limbs, without sensory manifestations, is presented. Investigation through magnetic resonance imaging demonstrated an extensive spinal ventral extradural cystic collection from C6 to T11. The lesion was approached through a laminectomy and a cyst-peritoneal shunt was introduced. The cyst reduced in size significantly and the patient is asymptomatic over a 48 months follow-up. This is the first reported case of a spontaneous ventral extradural spinal meningeal cyst causing cord compression. Cyst-peritoneal shunt was effective in the treatment of the case and it should be considered in cases in which complete resection of the cyst is made more difficult or risky by the need of more aggressive surgical maneuvers. Cistos meníngeos extradurais espinhais são formados tipicamente por estreita cápsula membranosa fibrótica, macroscopicamente semelhante a uma membrana de aracnóide, repleta de líquor e relacionada com uma raiz nervosa ou com a linha média posterior. Eles são extremamente raros em posição anterior e, quando ocorrem, habitualmente causam herniação da medula espinhal pela falha dural ventral. O caso de um homem de 61 anos de idade que iniciou com tetraparesia, espasticidade e hiperreflexia em membros inferiores, e flacidez com hipotrofia nos membros superiores, sem manifestação sensitiva, é apresentado. A investigação com ressonância magnética demonstrou extensa coleção cística extradural ventral à medula de C6 a T11. A lesão foi abordada diretamente via laminectomia com introdução de derivação cisto-peritoneal, reduzindo o cisto e tornando o paciente assintomático com um seguimento de 48 meses. Este é o primeiro caso relatado de cisto meníngeo extradural ventral espontâneo causando compressão medular. A derivação cisto-peritoneal se mostrou eficaz no tratamento do caso e deve ser considerada em situações em que a ressecção completa do cisto esteja impossibilitada, ou dificultada pela necessidade de manobras cirúrgicas mais agressivas e arriscadas.